2020
DOI: 10.1002/cncr.32939
|View full text |Cite
|
Sign up to set email alerts
|

New mammography screening performance metrics based on the entire screening episode

Abstract: BackgroundEstablished mammography screening performance metrics use the initial screening mammography assessment because they were developed for radiologist performance auditing, yet these metrics are frequently used to inform health policy and screening decision making. The authors have developed new performance metrics based on the final assessment that consider the entire screening episode, including diagnostic workup.MethodsThe authors used data from 2,512,577 screening episodes during 2005‐2017 at 146 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…It is possible that women who opted for a biennial screening strategy may have been included in the nonreceipt of screening group, despite participation in routine screening. 39,40 In the context of a prior report comparing outcomes of biennial versus annual screening, which indicated that premenopausal women receiving biennial screening were more likely to have tumors with less favorable prognostic characteristics, 18 our results highlighting an association between younger age and nonreceipt of screening are also in keeping with premenopausal women receiving screening at biennial intervals and may represent an opportunity to discuss annual screening intervals for younger women.…”
Section: Discussionsupporting
confidence: 72%
“…It is possible that women who opted for a biennial screening strategy may have been included in the nonreceipt of screening group, despite participation in routine screening. 39,40 In the context of a prior report comparing outcomes of biennial versus annual screening, which indicated that premenopausal women receiving biennial screening were more likely to have tumors with less favorable prognostic characteristics, 18 our results highlighting an association between younger age and nonreceipt of screening are also in keeping with premenopausal women receiving screening at biennial intervals and may represent an opportunity to discuss annual screening intervals for younger women.…”
Section: Discussionsupporting
confidence: 72%
“…The Breast Cancer Surveillance Consortium (BCSC) includes a network of breast imaging facilities in the United States that pool data for breast cancer research purposes via regional registries ( Ballard-Barbash et al, 1997 ; Breast Cancer Surveillance Consortium, 2021 ; Sprague et al, 2020 ). Participating facilities are linked by their agreements to contribute data to the registries and to a central Statistical Coordinating Center; there are no efforts to coordinate clinical operations or policy through the BCSC.…”
Section: Methodsmentioning
confidence: 99%
“…Digital breast tomosynthesis (DBT), available at 81% of US breast imaging facilities as of January 2022, was developed with the expectation that it would decrease recall rate and improve breast cancer detection in women with dense breasts (heterogeneously or extremely dense) by decreasing interval invasive cancer rates. Interval invasive and advanced breast cancer diagnoses are considered screening failures . Reducing screening failures is important because women with screening failures have worse survival and morbidity from treatment …”
Section: Introductionmentioning
confidence: 78%
“…We grouped prior benign diagnoses based on the highest level of risk as lobular carcinoma in situ greater than proliferative with atypia greater than proliferative without atypia greater than nonproliferative using published taxonomy or as unknown if a woman reported a prior biopsy with no available pathology result. Mammograms were classified as positive (BI-RADS 4 or 5 assessment) or negative (BI-RADS 1 or 2 assessment) based on final assessments after complete imaging workup . BI-RADS 3 final assessments were classified as positive because when cancer is present, short-interval follow-up imaging mostly leads to image-detected cancers …”
Section: Methodsmentioning
confidence: 99%